Adhesion property of bituminous crack sealants to different asphalt mixtures based on surface energy theory. (20th November 2020) - Sun, Zhilin; Li, Sitong; Zhang, Junhui; Zeng, Yi
Highlights: Adhesion of bituminous crack sealants to the crack wall was quantitatively evaluated. Correlation between adhesion indexes was verified by quantitative boiling method and SEM test. Weighted average adhesion work of cross-section was calculated and verified by the shear test. Abstract: In order to quantitatively evaluate the adhesion property of bituminous crack sealants to the crack walls formed by different types of asphalt mixtures, the surface energy components of raw materials were determined by the sessile drop method. Then the adhesion work of sealants and pavement materials was calculated respectively. The correlation between indexes of adhesion work was verified by quantitative boiling method and scanning electron microscope (SEM) test. Finally, four kinds of mixture specimens were formed, and the geometrical information of cross-section of mixture was extracted based on the digital image processing (DIP) technique. The weighted average adhesion work of the cross-section was calculated and verified by the shear tests. The test results show that the surface energy of basalt is obviously higher than that of the SBS modified asphalt and sealant. Among the components of surface energy of three materials, the dispersion component is dominant. The adhesion work of sealant and aggregate is higher than that of SBS modified asphalt. Test results of quantitative boiling method show that there is a good linear relationship between the mass loss rate of the sealant and the index of the adhesion work. The determination coefficient is as high as 0.96, indicating that the index of adhesion work can accurately characterize the adhesion performance of sealant and aggregate. DIP test results show that the aggregate of four mixtures accounts for the largest area, which exceeds 71% of total area. The relationship between the weighted average adhesion work of four mixtures and sealant A is AC-13 > AC-25 > SMA-13 > AC-20, which is consistent with results of the shear tests. The determination coefficient of linear correlation is 0.8672, which indicates that the proposed weighted average adhesion work can accurately characterize the actual adhesion state of interface.